A multi-parametric criteria for Tidal Energy Converters siting in marine and fluvial environments. (December 2017) - Zupone, G.Lo; Massaro, S.; Barbarelli, S.; Sulpizio, R.
Abstract: Marine renewable energy deployment involves site resource assessment as strategic support for installation and optimization. This part of the design needs to be based on best available measurement technologies and deployment methods, minimizing the investments. The siting and design of a kinetic energy converter (like a Tidal Energy Converter ones) require characterization of the variability of the flow velocity acting on the energy capture area in space and time, in order to assess the hydrodynamic forces, to design the structural loading and power capacity of the TEC, helping investment decisions and project financing. In this work, a site assessment procedures for emplacement of TEC machines are shown, comparing sites with different hydrogeological characteristics using the same design approach. In order to define the best conditions for siting, three case studies have been carried out, two for sea and last for river installation. The strait of Messina (Italy), a marine channel with an amphidromic point for the tides, has its minimum depth at 72 m, between Ganzirri and Punta Pezzo, deepening to 1000 m to the North East and down to 2000 m to the South. The Cook Inlet (Alaska), a large subarctic estuary in South-central Alaska which extends about 250 km from Anchorage bay to the Pacific Ocean. Tidally dominated currents control the hydrographic regime, meanwhile water levels and currents are influenced by tides coming from the Gulf of Alaska, which are significantly amplified as approaching Anchorage bay. The Pearl River Estuary and its adjacent coastal waters (China) have a length of about 70 km, a width of about 15 km and an average depth of about 4.8 m, but it has a depth of more than 20 m in its eastern part.